Status Harta Pusaka dan Harta Pencaharian dalam Sistem Mayorat Laki-Laki Masyarakat Lampung Pepadun Perspektif Kompilasi Hukum Islam - Lu’lu’ Salamah; Abd Rouf (Lembaga Yasin AlSys, 2026)
Although the male primogeniture system in the Lampung Pepadun community has become an important part of customary identity, normative issues arise when the eldest son is positioned as the successor to customary status and manager of all inherited property without distinguishing between the status of ancestral property and acquired property. This study aims to analyze the position of ancestral property and acquired property in the male primogeniture system of the Lampung Pepadun community and their legal status under the Compilation of Islamic Law. This study used a normative legal method with statutory, conceptual, and limited comparative approaches. Legal materials were collected through library research and analyzed qualitatively. The results show that communal ancestral property can continue to be maintained under customary management by the eldest son as penyimbang, as long as it is not interpreted as absolute private ownership. Conversely, the legal status of acquired property needs to be examined as either personal property or joint marital property. If the acquired property is classified as joint marital property, the surviving spouse’s share must first be separated before the deceased’s share is distributed to the heirs. The conclusion of this study affirms that the male primogeniture system can still be maintained as the customary identity of the Lampung Pepadun community, but its application must be limited so that it does not eliminate the rights of spouses and heirs under the Compilation of Islamic Law. These findings contribute to the development of studies on customary inheritance law and Islamic law and imply the importance of harmonizing customary inheritance practices with the principles of justice in Islamic family law.